2007
DOI: 10.5860/crl.68.6.472
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Use of Federated Searching: A Survey of Preferences and Perceptions of Value-added Functionality

Abstract: Randomly selected undergraduates at BrighamYoung University, Brigham Young University-Idaho, and Brigham Young University-Hawaii, all private universities sponsored by The Church of Jesus Christ of Latter-day Saints, participated in a study that investigated four questions regarding federated searching: (1) Does it save time? (2) Do undergraduates prefer it? (3) Are undergraduates satisfied with the results they get from it? (4) Does it yield higher-quality results than nonfederated searching? Federated search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Several articles have presented usability studies results for various federated searching products. 6 Fagan provided a thorough literature review of faceted browsing and next-generation catalogs. 7 Western Michigan University presented usability study results for the next-generation catalog VuFind, revealing that participants took advantage of the simple search box but did not use the next-generation catalog features of tagging, comments, favorites, and SMS texting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several articles have presented usability studies results for various federated searching products. 6 Fagan provided a thorough literature review of faceted browsing and next-generation catalogs. 7 Western Michigan University presented usability study results for the next-generation catalog VuFind, revealing that participants took advantage of the simple search box but did not use the next-generation catalog features of tagging, comments, favorites, and SMS texting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Students are not interested in information quality; instead they are focused on finding full text articles and finishing research as quickly as possible. Students in a study by Belliston, Howland, and Roberts (2007) described a federated search as "faster, easier, simpler, and more efficient" (p. 478).…”
Section: Literature Reviewmentioning
confidence: 97%
“…A number of recently published studies (Williams, Bonnell, & Stoffel, 2009;Korah & Cassidy, 2010;Armstrong, 2009;Belliston, Howland, & Roberts, 2007) have examined student perceptions of federated search tools and their preferences regarding different research tools. These studies have found that undergraduates prefer federated searching to individual databases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other studies have explored the issue of student satisfaction with their research experience (Belliston, Howland, & Roberts, 2007;Martzoukou, 2008) and their satisfaction with library services (Gardner & Eng, 2005;Harwood & Bydder, 1998;Voelker, 2006). Findings suggest that students are generally happy with their research and library experiences (Gardner & Eng, 2005) but often prefer the convenience of their own homes when conducting research (Vondracek, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%